2017
DOI: 10.7567/jjap.56.06ha02
|View full text |Cite
|
Sign up to set email alerts
|

Progress and prospects in nanoscale dry processes: How can we control atomic layer reactions?

Abstract: In this review, we discuss the progress of emerging dry processes for nanoscale fabrication. Experts in the fields of plasma processing have contributed to addressing the increasingly challenging demands in achieving atomic-level control of material selectivity and physicochemical reactions involving ion bombardment. The discussion encompasses major challenges shared across the plasma science and technology community. Focus is placed on advances in the development of fabrication technologies for emerging mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 205 publications
(239 reference statements)
0
23
0
Order By: Relevance
“…Over the past few years, several authors have suggested coupling ALD with ALE to create new “atomic scale processes,” ,, but results demonstrating feasibility, benefits, and challenges of integrated ALD and ALE have not been reported so far. This work demonstrates for the first time that thermal ALD and thermal ALE can be successfully integrated under low-temperature isothermal conditions in a single vapor-phase reactor to achieve highly selective deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, several authors have suggested coupling ALD with ALE to create new “atomic scale processes,” ,, but results demonstrating feasibility, benefits, and challenges of integrated ALD and ALE have not been reported so far. This work demonstrates for the first time that thermal ALD and thermal ALE can be successfully integrated under low-temperature isothermal conditions in a single vapor-phase reactor to achieve highly selective deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Between the alternating half-cycles, an inert gas is used to purge the reactor, 1 removing the previously-entered precursor from the chamber prior to the next precursor pulse, in order to avoid undesirable reactions and to ensure high film quality [6]. Thus, the ALD method is capable of uniformly growing materials layer-by-layer on complex substrate geometries in a more precise and more controllable manner [7][8][9][10]. As a result, ALD has demonstrated its great potential in the field of microelectronics manufacturing, where 3D ultra-thin and highly-conformal films are becoming increasingly crucial.…”
Section: List Of Figuresmentioning
confidence: 99%
“…However as this approach is predicted to reach the ultimate limit within a few years, only novel materials (Beyond Moore) and system diversity like sensor integration or truly 3D techniques (More Than Moore) can further increase chip density or functionality per cubic centimeter. To have a better understanding of current technology drivers and near future trends or needs, the reader is invited to read a few of the latest review papers on these subjects and the final International Roadmap for Semiconductors ITRS 2015 or the more recent IRDS roadmaps [1][2][3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%